Dynamic effects of a single fiber break in unidirectional glass fiber-reinforced polymer composites: Effects of matrix plasticity. (June 2018) - Ganesh, Raja; Sockalingam, Subramani; Gillespie, John W
In a unidirectional composite under static tensile loading, breaking of a fiber is shown to be a locally dynamic process, leading to stress concentrations in the matrix and neighboring fibers and debonding of the interface, which can propagate at high speed over long distances. In our previous work, a fiber break within a two-dimensional fiber array embedded in elastic epoxy matrix (with cohesive interface) was modeled to quantify the effects of these dynamic stresses. The results indicated that the elastic limit of the polymer matrix can be exceeded. In this study, the effects of matrix plasticity on dynamic stress concentrations due to a single fiber break are investigated. For the range of matrix yield stresses considered, the dynamic stress concentrations are significantly higher than corresponding values predicted by a quasi-static model with a pre-broken fiber. Based on the ratio of shear yield strength of the matrix and mode II peak traction of the interface cohesive law, two distinct regimes of damage are shown to exist. Only matrix yielding occurs when this ratio is less than 1.0, while both interfacial debonding and matrix yielding occur when it is greater than 1.0. At higher fiber break strengths, where the elastic matrix model predicts unstable interfacial debonding, reduction in matrix yield strength leads to a transition to stable debonding and arrest. Reducing the matrix yield strength also leads to a lowering of the peak dynamic stress concentrations in adjacent fibers, while spreading the stress concentrations over a larger volume of the composite microstructure.